A model for sustainable solid waste management through an analysis of Chicago, Illinois solid waste management systems - Raglin, Kala N. (Kansas State University, 2013)
America’s landfill space is quickly depleting as the population continues to experience rapid growth; as the population grows the amount of daily waste generated increases at an alarming as well. In fact, by the year 2024, America would have exhausted all land areas dedicated to landfills. Currently, nationwide mandated regulations or standards to decrease the amount generated solid waste, construction waste, composting waste, or reducing waste at the source; do not exists. The following report researches effective practices that would make a waste management system sustainable. In order to rate the sustainability of the management system, a score sheet was created drawing from literature written. By creating a score sheet, individual waste management systems are able to determine if they are indeed sustainable and/or in need of improvement. The City of Chicago, Illinois, was chosen as the city to be measured and has proven to have a promising future as a prototype in effective sustainable waste management practices.
Keywords: Waste management; Sustainable waste practices; Engineering, Sanitary and Municipal (0554)